EU DIGITAL SPACE: NORMS AND STANDARDS - Подоляк, Світлана; Мельник, Володимир (SWorldJournal, 2024)
Digital transformation is transforming every aspect of modern life today, and the European Union is actively adapting to these changes by focusing on creating a digital single market. This article examines not only the purpose, but also the key components